Peran Fintech Syariah dalam Meningkatkan Inklusi Keuangan di Indonesia - Elly lestari; Cory Vidiati (STKIP Subang, 2026)
Financial technology, or fintech, has transformed the global financial system, including Indonesia. Sharia fintech has emerged as an alternative that can meet public demand for fast, easy, and Sharia-compliant financial services. The purpose of this study is to examine how Sharia fintech contributes to increasing financial inclusion in Indonesia, particularly by targeting communities underserved by formal financial institutions. A descriptive-analytical method was used to investigate various regulations, fintech industry reports, and national financial inclusion data. The results show that Sharia fintech helps increase access to financial services through peer-to-peer financing, Sharia payment services, and Sharia-compliant digital banking. Sharia fintech also supports government programs to achieve financial inclusion by improving public financial literacy. However, several issues remain, such as regulation, digital literacy, and consumer protection. Sharia fintech has the potential to be a key driver in realizing an inclusive, equitable, and sustainable financial system in Indonesia. This can be achieved through strengthened regulations, public education, and Sharia-compliant product innovation.